Fungal Rhinosinusitis: An Overview - Rajat Saini; Vishwambhar Singh; Sanjay Kumar Saroj; Ashvanee Kumar Chaudhary; Rajesh Kumar; Siva S.; Ram Raj Yadav; Shishupal Yadav; Silky Silky; Deepak Kumar Gupta; Arpit Goyal; Akshat Panday (NMO Journal)
Fungal rhinosinusitis (FRS) once considered a rare disease. This global rise in the burden of fungal disease is a consequence of an increment in the population with weakened immune systems. Increased life expectancy with rise in conditions like diabetes mellitus, medical advancements with invasive interventions, use of steroid, wider uses of broad-spectrum antibiotics, immunosuppressive treatments for transplantation and autoimmune diseases, increased incidence of immune deficiency disease. Fungal infections of the paranasal sinuses are in fact a spectrum of diseases rather than one distinct entity. As such, there has been much published on the classification of fungal rhinosinusitis (FRS). Early classifications of FRS used the causative organism as the descriptor, i.e., aspergillosis, mucormycosis, etc. Rapid diagnosis and prompt treatment may save at least some of these patients. When fever with neutropenia and sinonasal symptoms are seen in patients with impaired immune function maintaining a high index of suspicion is essential, and the appropriate diagnostic work up should involve imaging studies and nasal endoscopy with a possible biopsy so as to initiate treatment in a timely manner. Clinical and histopathologic features of fungal rhinosinusitis are specific to each form, and criteria for diagnosis have been developed. This review of fungal sinus diseases summarizes invasive and noninvasive fungal rhinosinusitis forms but concentrates on AFS because of its high prevalence and the fundamental role the allergist-immunologist plays in its diagnosis and treatment.